Advanced Technologies in Practical Applications for National Security (Studies in Systems, Decision and Control, 2018)
This book presents advanced technologies used in practice to enable early recognition and tracking of various threats to national security. It discusses practical applications, examples and recent challenges in the application fields using sophisticated sensory devices, embedded designs and airborne and ground unmanned vehicles. Undeniably rapid advances in the development of sophisticated sensory devices, significant increases of computing power available to embedded designs and the development of airborne and ground unmanned vehicles offer almost unlimited possibilities for fighting various types of pathologies affecting our societies. The book provides scientists, researchers, engineers and graduate students involved in computer vision, image processing, data fusion, control algorithms, mechanics, data mining, navigation and integrated circuit (IC) with numerous valuable, useful and practical suggestions and solutions.